Modern Approaches to Teaching Foreign Languages in Technical Higher Education Institutions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses modern approaches to teaching foreign languages ​​in technical universities. The requirements for graduates of technical universities are high, but they are justified because they allow them to be competitive in the labor market.